PENGARUH LITERASI KEUANGAN, INOVASI, DAN PERAN PEMERINTAH TERHADAP PENGEMBANGAN USAHA KECIL DAN MENENGAH - Yolanda Iqnatia (2020)
This research is a quantitative study that aims to determine the effect of financial literacy, innovation, and the role of government in the development of SMEs. The population in this study are SMEs in the District of Cipayung, East Jakarta. The sample size was taken as many as 100 samples, with non-probability sampling method in particular is Purposive Sampling. Data collection was carried out through questionnaires with a sample of 100 respondents. The analysis technique used is the Partial Least Square (PLS) analysis method. the results of this study indicate that (1) financial literacy has no significant effect on the development of SMEs with a path coefficient of 0.051. (2) innovation has a significant influence on the development of SMEs with a path coefficient of 0.77. (3) the role of government has a significant effect on the development of SMEs with a path coefficient of 0.178.